Neuropeptide Y resists excess loss of fat by lipolysis in calorie‐restricted mice: a trait potential for the life‐extending effect of calorie restriction - Park, Seongjoon (Aging Cell, 2017)
Neuropeptide Y (NPY) is an orexigenic peptide that plays an essential role in caloric restriction (CR)‐mediated lifespan extension. However, the mechanisms underlying the NPY‐mediated effects in CR are poorly defined. Here, we report that NPY deficiency in male mice during CR increases mortality in association with lipodystrophy. NPY (−/−) mice displayed a rapid decrease in body weight and fat mass, as well as increased lipolysis during CR. These alterations in fat regulation were inhibited by the lipolysis inhibitor, acipimox, a treatment associated with reduced mortality. The lipolytic/thermogenic signaling, β3‐adrenergic receptor/hormone sensitive lipase, was markedly activated in white adipose tissue of NPY (−/−) mice compared with that of NPY (+/+) mice, and thermogenesis was controlled by NPY under negative energy balance. These results demonstrate the critical role of NPY in the regulation of lipid metabolic homeostasis and survival via control of lipolysis and thermogenesis in a state of negative energy balance.